2018
DOI: 10.1111/epi.14036
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic subtype of hippocampal sclerosis and episodic memory performance before and after temporal lobectomy for epilepsy

Abstract: This is the largest reported overall sample and the largest subset of patients with HS ILAE type 2. Group data suggest that patients with HS ILAE type 2 perform better on preoperative memory measures, but individually there were no differences in the magnitude of memory impairment. Following surgery, there were no statistically significant differences between groups in the proportion of patients who declined. Future research should focus on quantitative measurements of hippocampal neuronal loss, and multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…The replication of this relationship confirms the association between total hippocampal volume and episodic memory performance in aging. Prior data in patient populations with hippocampal sclerosis and hippocampal degeneration have also demonstrated the role of hippocampal volume in episodic memory (Sexton et al, 2010;Saghafi et al, 2018). However, our larger sample did not show a relationship between total hippocampal volume and processing speed, which O'Shea et al (2016) found to be at near the same magnitude as episodic memory.…”
Section: Total Hippocampal Volume and Nihtb-cbcontrasting
confidence: 64%
“…The replication of this relationship confirms the association between total hippocampal volume and episodic memory performance in aging. Prior data in patient populations with hippocampal sclerosis and hippocampal degeneration have also demonstrated the role of hippocampal volume in episodic memory (Sexton et al, 2010;Saghafi et al, 2018). However, our larger sample did not show a relationship between total hippocampal volume and processing speed, which O'Shea et al (2016) found to be at near the same magnitude as episodic memory.…”
Section: Total Hippocampal Volume and Nihtb-cbcontrasting
confidence: 64%
“…Given the disparities between clinical series, there is no consensus on whether neuronal loss progresses over time (Bl€ umcke et al, 2009;Davies et al, 1996). In addition, individual variabilities and anatomical inhomogeneities complicate classification (Coras et al, 2014;Rodrigues et al, 2015;Saghafi et al, 2018). For instance, patchy neuronal loss has been described in the CA1 region in some cases, whereas in others, it seems to adopt a more laminar profile (Prada Jardim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In patients presenting types I and III, there is also neuronal loss in the dentate gyrus (DG) and, to a lesser extent, in CA3, contributing to a more severe loss of mnemonic function, which practically disappears if the loss of granule cells is higher than 60% ( 16 ). Nonetheless, other authors have reported that while patients with type II MTLE-HS pathology showed better group memory performance than those with type I MTLE-HS, almost half of them exhibited moderate to severe impairment in episodic memory tests ( 17 20 ).…”
Section: Introductionmentioning
confidence: 89%